Estimation of the calcium metabolism dynamics for brain ischemic patients using atomic-emission spectrometry of human hair - Patapovich, Mariya P.; Buloichik, Janne I.; Pashkovskaya, Irina D.; Nechipurenko, Nataliya I.; Zajogin, Anatoli P. (Journal of the Belarusian State University. Physics, 2017)
Analysis of human hair by means of the multichannel atomic-emission spectrometry method has been performed to estimate metabolism of the essential elements in organism of the patients with (cerebrovascular) brain ischemia. Owing to this highly sensitive and fast method, the quantitative variations in the content of these elements may be detected for long periods of time. Quantitative estimates of the elemental content in hair point to the relationship between the course of the disease under study and variations in the content. It has been shown that the critical period in the course of this disease may be due to the lowered calcium levels. Prompt and effective estimation of the metabolism dynamics is useful for timely prevention of critical conditions. The proposed techniques may be used for early diagnostication and prevention of the brain ischemia.